Hubungan Kemampuan Membaca Pemahaman Dengan Kemampuan Menyelesaikan Soal Cerita Matematika Kelas V SD - Fauziah, Nursifa; Hadi, Waluyo; Sari, Yofita (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2024)
The ability to read comprehension becomes very important for students to understand the lessons in school. To complete a mathematical story, a full understanding of the subject matter is required so that the student can answer the question correctly. The aim of this study was to find out if there was a relationship between reading ability and understanding and the ability to solve mathematical stories. The type of research used is quantitative research with correlational approaches. The results showed that the Sig. (2-tailed) value is 0.014, meaning that there is a relationship or correlation between the variables x and y. The product moment correlation test showed that the Pearson Correlation value is 0.554 which means a positive relationship. From the data test, it can be concluded that there is a positive relationship between the ability to read comprehension and ability to complete mathematical stories of students V grade SDN Kemayoran 13.